2012
DOI: 10.1097/cji.0b013e31826f79c8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Stem Cell Antigens as Consolidative Active Specific Immunotherapy

Abstract: Only 10% of metastatic melanoma patients survive 5 years, even though many can achieve substantial tumor reduction by surgical resection and/or radiation therapy and/or systemic therapy. An effective, nontoxic, consolidation immunotherapy could benefit such patients. We initiated a randomized trial to compare 2 promising patient-specific immunotherapy cell products. Patients had to have a diagnosis of metastatic melanoma and availability of an autologous melanoma cell line. Patients were stratified by whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…Although most of them are still in the phase of preclinical in vitro and in vivo models, a number of potential cancer immunotherapies have reached a phase III clinical trials in the last 25 years [29]. Dendritic cells-based vaccination with the potential to boost cancer-specific effector T cells and target CSCs, like those for glioblastoma and melanoma, are either in preclinical in vitro phase [30, 31] or in clinical phase I or II [32, 33]. The only DC-based vaccine approved by the Food and Drug Administration (FDA) is Provenge for prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of them are still in the phase of preclinical in vitro and in vivo models, a number of potential cancer immunotherapies have reached a phase III clinical trials in the last 25 years [29]. Dendritic cells-based vaccination with the potential to boost cancer-specific effector T cells and target CSCs, like those for glioblastoma and melanoma, are either in preclinical in vitro phase [30, 31] or in clinical phase I or II [32, 33]. The only DC-based vaccine approved by the Food and Drug Administration (FDA) is Provenge for prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These include an oncolytic vaccinia virus encoding GM-CSF [91], autologous dendritic cells and allogeneic whole tumor cells encoding GM-CSF [92-94], adjuvant GM-CSF following vaccination with peptide or RNA encoding melanoma peptides [95,96] and autologous dendritic cell or whole tumor cell vaccines [97], and GM-CSF DNA vaccines [98]. …”
Section: Reviewmentioning
confidence: 99%
“…The type of radiation may affect vaccine development as gamma-radiation (at 200 Gy) was shown to yield different immunologic effects on melanoma cells than other forms of non-ionizing radiation (32). A randomized phase II study of patients with metastatic melanoma demonstrated improvements in overall survival with autologous DCs loaded with antigens from irradiated autologous patient-specific proliferating melanoma cells, compared to irradiated autologous patient-specific proliferating tumor cells (33). Interestingly, a multivariable analysis of patients treated with the aforementioned DC therapy revealed that prior radiotherapy for melanoma was associated with improved survival (34).…”
Section: Introductionmentioning
confidence: 99%